Ein hermeneutischer Konstruktionsentwurf sozialer Systeme - Hans-Christian Krcal (University of Heidelberg, Department of Economics, 2013)
– The paper handles central topics of social system theory, such as contingency,emergence, communication, reality construction based on cognitive epistemology, and differential logic. The conducted discussion is embedded in the construction of a hermeneutic approach to social system theory. Communication is a decisive part of economic systems, but often it is not object of scientific research on economic topics. Even informal business communication is seldom part of economic terms and models. To understand the meaning of social systems from a firms' and methodological perspective we must develop a phase scheme driven by communication, because of their decisive structural role for social systems. Hermeneutic means hereby, from an observer's point of view, a kind of didactical, philosophical opening of business life experiences – it is much more than pure text interpretation. Hence, the observer of social systems has to redefine his own language based preconditions of understanding social systems communication.
urn:nbn:de:bsz:16-heidok-151517
Keywords: 330; social system; communication; hermeneutic approach to social system structure